Pragmatic Failures in Japanese Conversations Among Beginner Japanese Language Learners Leading to Face-Threatening Acts - Yogyanti, Devita Widyaningtyas; Atiqah, Annisa Nurul; Iswahyuni, Dwi; Sari, Angela Bayu Pertama; Rejeki, Sri (Vocational College of Diponegoro University, 2024)
This research aims to identify the types of pragmatic failures that occur in beginner-level Japaneselanguage classes. The data was taken from conversation texts created by students in groups over one semester from two different universities. The utterances in the conversation text that were perceived to contain pragmatic failure were categorized and then verified through interviews with nativeJapanese speakers to understand the impressions they felt when hearing such utterances. Verifiedutterances containing pragmatic failure were then categorized into pragmalinguistic failure andsociopragmatic failure. It was discovered that even in simple contexts like self-introductions, therewere many pragmatic failures that had the potential to become Face Threatening Acts (FTA) againstthe positive and negative face of the interlocutor. In the case of basic Japanese students,pragmalinguistic failures are more commonly found than sociopragmatic failures. However, bothpragmalinguistic and sociopragmatic failures tend to be more of a face-threatening act against thepositive face of the interlocutor. The research finding reveals the linguistic characteristics thatthreaten the interlocutor's positive face include using first-person pronouns excessively,discriminatory questions about origin, and misusing specific Japanese words like